ANALISIS PENGARUH TEKNOLOGI TERHADAP EFEKTIVITAS ASESMEN PERKEMBANGAN SOSIAL-EMOSIONAL ANAK USIA DINI - Yusria; Sri Hartati; Siti Safitri; Nanda Rizki Wildani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the impact of technology use on the effectiveness of social development assessments in early childhood. The issues addressed include the challenges of integrating technology into the decision-making process and early childhood education (ECE) teachers’ perspectives on its use. The method employed in this study is a qualitative descriptive approach based on literature review, focusing on various relevant scientific sources from the past ten years. The results indicate that interactive technologies, such as educational applications and digital games, can enhance children's engagement and facilitate more efficient data collection. However, the study also identifies challenges, such as potential dependency on technology and reduced social interaction, which may hinder child development. Therefore, training for educators in the effective use of technology is crucial to improving the quality of education and social assessment in children. This research is expected to contribute both theoretically and practically to the development of more accurate and contextual assessments, and serve as a guide for policy-making in promoting the targeted use of technology in early childhood education.